Efektivitas Penggunaan Aplikasi Sistem Keuangan Desa (Siskeudes) dalam Pengelolaan Keuangan ditinjau dari Perspektif Akuntansi Syariah (Studi Kasus Desa Mulamenre`E, Kecamatan Ulaweng, Kabupaten Bone) - Faramillah Anugrah; Rini Idayanti; Hartas Hasbi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of the Village Financial System (SISKEUDES) application in financial management from a Sharia accounting perspective. The current rapid development is technological advancement, which has become a necessity, particularly in financial management. Previously known as the Regional Management Information System (SIMDA), the Village Financial System (SISKEUDES) application was then introduced. This study used a qualitative method with a field approach, involving interviews and observations with parties responsible for and directly involved in managing village finances. The results indicate that the effective use of the Village Financial System (SISKEUDES) application in Mulemenre Village provides a positive and structured contribution to village financial management, but its implementation is not yet fully optimal. From a Sharia accounting perspective, village financial management through the Village Financial System application reflects three main principles: accountability, fairness, and truth